Early maritime cultures in East Africa and the Western Indian Ocean : papers from a conference held at the University of Wisconsin-Madison (African Studies Program) 23-24 October 2015, with additional contributions - Sarathi, Akshay (Access archaeology., 2018)
This work represents a multi-disciplinary effort to examine East Africa and the Western Indian Ocean. Multiple lines of evidence drawn from linguistics, archaeology, history, art history, and ethnography come together in novel ways to highlight different aspects of the region's past and offer innovative avenues for future research.